Modelo de implementación de herramientas lean manufacturing para el proceso de producción de postres de microempresas de la ciudad de Bogotá D.C. (2020)
In the present project, an implementation model of Lean Manufacturing tools was carried out for the process of production of desserts of micro-companies in the city of Bogotá DC, a model that aims to establish the current situation of companies in the aforementioned sector, in a way that facilitates the identification of waste (muda) and opportunities for improvement, allowing to increase their productivity through five lean manufacturing tools that were selected according to the characteristics of the sector and subsector. For the development of the research, a conceptual framework of Lean Manufacturing was carried out where the types of waste were established and how they negatively influence the productive processes of companies, as well as mentioning the main Lean Manufacturing tools and the impact of each of them on the production area. Subsequently, to diagnose the current state of the confectionery and pastry sector, the PESTAL tool was used (Bogotá and Colombia), then the sector analysis was carried out where the diagnosis was completed using the DOFA Matrix tool (weaknesses, opportunities, strengths and threats).